Personalized E-learning - Deng, Joseph Lide (2010)
E-learning has truly evolved over the past ten years or so. Technology-enabled learning and distance education changed to online learning and web-based training, which morphed into e-learning. The introduction of e-learning added new meaning to training, and the possibilities for delivering knowledge and information to learners at an accelerated pace opened a new world for knowledge transfer. By now, industry pioneers agree that e-learning is here to stay.